Sedation practice: is it time to wake up and embrace change? - Regan, Kate (BioMed Central, 2008)
Recommendations for sedation regimes in the intensive care unit (ICU) have evolved over the last decade based on findings that relate the clinical approach to improved patient outcomes. Martin and co-workers conducted two surveys into German sedation practice covering the time period during which these changes occurred and as such provide an insight into how these recommendations are being incorporated into everyday clinical practice.